CHANGING THE LEGAL WORLD – ARTIFICIAL INTELLIGENCE AND COMMERCIAL INTERMEDIARY CONTRACTS - Žaklina Spalević; Jelena Belović; Jelena Jakšić (Pravo)
Artificial intelligence poses a challenge to modern legal systems, as it represents a societal phenomenon and an extension of social reality. Aware that social reality is rapidly evolving due to technological progress, we rightfully question whether the existing legal frameworks are sufficient and adequate to accommodate the changes occurring in the field of artificial intelligence. Specifically, legal subjects include natural persons and legal entities. Can we still limit ourselves to only these two categories today, when computers equipped with cutting-edge artificial intelligence programs increasingly play a significant role in making decisions with legal consequences? This paper will focus on analyzing contemporary social trends and their impact on the existing legal framework, utilizing an evolutionary interpretation of legal institutes. Through the example of natural and legal persons acting as intermediaries in the provision of services, specifically in transportation, we will examine this phenomenon and potential future developments. In this context, the paper will focus on judicial practice related to the Uber case.